Hyperlactatemia caused by intra-venous administration of glycerol: A case study - Katayama, Shinshu (Medknow Publications & Media Pvt Ltd, 2012)
Glyceol(®) is an intracranial pressure reducing agent composed of 5% fructose and concentrated glycerol. Although rapid administration of fructose is known to cause lactic acidosis, little is known about hyperlactatemia caused by Glyceol(®) administration itself in adults. We observed an adult case of hyperlactatemia occurred after administration of 200 mL of Glyceol(®) over a period of 30 minutes. Since there was no evidence of an underlying liver disease or metabolic abnormality, and no findings of sepsis or impaired tissue perfusion, the cause of this condition was deemed to be the rapid loading of fructose contained as a constituent of Glyceol(®). We then performed a retrospective chart review and found other 9 cases admitted to Jichi Medical University Hospital ICU and administered Glyceol(®) during the past year. Their lactate levels increased in general, peaked approximately 45 minutes after Glyceol(®) administration and returned to pre-administration levels around 3 hours after. Although hyperlactatemia is an important indicator of sepsis and impaired tissue perfusion, caution is required when performing such an assessment in patients being administered Glyceol(®).